DETERMINAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY: STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nanda Amelia Jauhari; Fajar Satriya Segarawasesa (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2021)
This study aims to analyze and provide empirical evidence on the effect of firm age, foreign ownership, board of commissioners, audit committee, and industry type on corporate social responsibility disclosure. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange during 2017-2019, totalling 180 companies. The sampling technique used is the purposive sampling method with a total sample of 96 companies that met the criteria for the research samples. This study applies a quantitative approach with secondary data types. Data collection uses documentation techniques. Data analysis uses descriptive analysis and multiple regression analysis employed SPSS version 21 program. The results show that the company’s age, the board of commissioners and the type of industry have a positive effect on the disclosure of corporate social responsibility, while foreign ownership and the audit committee do not affect the corporate social responsibility disclosure.